Gesundheit & Bewegung - Korsten-Reck U (Dynamic Media Sales Verlag, 2016)
To protect the health of athletesis a general goal of the International Olympic Committee (IOC). This includes the update of the Female Athlete Triad. This Consensus Statement provides the guidelines to manage risk assessment, treatment and return-play-decision. In the Version of 2014,the term of female Athlete Triad introduces a broader more comprehensive term Relative Energy Deficiency in Sport (RES). The term points to the complexity involved and the fact that males are also affected. The cause of this syndrome is energy deficiency relative to the balance between dietary energy and energy expenditure required for health and activities of daily life, growth and sports performance. Psychological consequences can either precede RED-S or can be the result. The clinical phenomenon is not a triad of the three entities of energy availability, menstrual function and bone health, but rather a complex syndrome that affects many aspects of physiological, psychological and athletic performance. The broader term included in this Consensus Statement also recommends practical clinical models for management of affected athletes. The Sport Risk Assessment and Return to Play Model includes three groups with respective clinical recommendations. KEY WORDS: Eating Disorder, Energy Availability, Energy Deficiency, Athletes